THE IMPROVEMENT OF THE SOCIAL PIETY AS A THANKSGIVING SENSE TO ALLAH SWT IN THE MOMENT OF THE SLAUGHTER AND DISTRIBUTION OF THE KURBAN IN EID ADHA 1436 H - Roestamy, Martin (Universitas Djuanda, 2015)
The improvement of the social piety as a thanksgiving to Allah SWT would be this years theme. The essence of the theme is the nature of obedient to Allah SWT and an awareness of the importance of maintaining human relationship. The important of being grateful for the fortune given by Allah SWT, so the Muslim would be stronger faith and brotherhood. The slaughtering and distribution was held on Friday 25 September 2015 in Bogor Djuanda University as a role processes of Ied Adha in Bogor Djuanda University. The activity was conducted by the cooperation of foundation of Amaliyah, LPPM Bogor Djuanda University, and DPP Al-Ittihadiyah. The slaughtering was begun at 05.30 a.m. First, checking the condition of the animals by the husbandary lectures and students. Then, the distribution was done by the coupon. The data showed that 137 receiver from the employee, students, PKD in Bogor Djuanda University, and some corporate institution such as BTN Syariah, BJB, and Polsek Ciawi. 18 cows and 11 goats were distributed to 2000 peoples around Bogor Djuanda University (Gadog, Tipas, Warung Seri, and Sindangsari).